Crisis communication strategies : how to prepare in advance, respond effectively and recover in full / Amanda Coleman - Coleman, Amanda
"Crisis communication is high stakes work. For communications managers and PR professionals, it's likely to be the most stressful time of their working life. Crisis Communication Strategies is a must-have handbook for laying the groundwork before a crisis hits, meaning that when the inevitable day comes, the company already has policies and procedures in place to leap into meaningful action without delay. Crisis Communication Strategies is unique in the way it equips readers to deal with any kind of crisis - whether caused by internal error, customer action, natural disasters, terrorism or political upheaval. Moving chronologically, the book opens by looking at the skills, policies and procedures that should be set up in advance, during times of normal business operations. It then moves on to look at how those procedures can be activated when a crisis occurs and during the immediate response. Finally, it delivers strategies for true long-term recovery for both the company itself and, where necessary, the wider community. Packed with actionable tips, checklists and global case studies, Crisis Communication Strategies is the essential guide to protecting your company and building true, long-term resilience"--